ENDOTHELIAL DYSFUNCTION AND ITS CORRECTION WIT CYTOPROTECTORS IN PATIENTS WITH STABLE EFFORT ANGINA AND ARTERIAL HYPERTENSION - F. E. Khlebodarov; P. Yu. Turikov; V. P. Mikhin (Российский кардиологический журнал, 2009)
The study compared the effects of cardiocytoprotectors (mildronate, trimetazidine) on endothelial function, physical stress tolerability, and circadian blood pressure (BP) profile in patients with arterial hypertension (AH; n=60) and stable angina (n=82), receiving anti-anginal therapy (beta-adrenoblockers, nitrates) or antihypertensive therapy (enalapril). Adding cardiocytoprotectors to the complex therapy improved endothelium-dependent vasodilatation and circadian BP profile, as well as reduced endothelial dysfunction severity and intima-media thickness in AH patients. Mildronate was more effective in improving endothelial structure and function.